Measurement of the lifetime and Λ separation energy of 3ΛH - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; et al. (Physical review letters, 2023)
The most precise measurements to date of the 3ΛH lifetime τ and Λ separation energy BΛ are obtained using the data sample of Pb-Pb collisions at √sNN=5.02 TeV collected by ALICE at the LHC. The 3ΛH is reconstructed via its charged two-body mesonic decay channel (3ΛH→3He+π− and the charge-conjugate process). The measured values τ=[253±11(stat)±6(syst)] ps and BΛ=[102±63(stat)±67(syst)] keV are compatible with predictions from effective field theories and confirm that the 3ΛH structure is consistent with a weakly bound system.